Bariatric surgery for diabetic comorbidities: A focus on hepatic, cardiac and renal fibrosis - Ding, Huanxin; Zhang, Yun; Ma, Xiaomin; Zhang, Zhongwen; Xu, Qian; Liu, Chuxuan; Li, Bingjun; Dong, Shuohui; Li, Linchuan; Zhu, Jiankang; Zhong, Mingwei; Zhang, Guangyong (Frontiers in Pharmacology, 2022)
Continuously rising trends in diabetes render this disease spectrum an epidemic proportion worldwide. As the disease progresses, the pathological effects of diabetes may impair the normal function of several vital organs, eventually leading to increase the risk of other diabetic comorbidities with advanced fibrosis such as non-alcoholic fatty liver disease, diabetic cardiomyopathy, and diabetic kidney disease. Currently, lifestyle changes and drug therapies of hypoglycemic and lipid-lowering are effective in improving multi-organ function, but therapeutic efficacy is difficult to maintain due to poor compliance and drug reactions. Bariatric surgery, including sleeve gastrectomy and Roux-en-Y gastric bypass surgery, has shown better results in terms of prognosis for diabetes through long-term follow-up. Moreover, bariatric surgery has significant long-term benefits on the function of the heart, liver, kidneys, and other organs through mechanisms associated with reversal of tissue fibrosis. The aim of this review is to describe the impact of type 2 diabetes mellitus on hepatic, cardiac and renal fibrosis and to summarize the potential mechanisms by which bariatric surgery improves multiple organ function, particularly reversal of fibrosis.